Non-linear creep of polypropylene utilizing multiple integral - Mahmoud Fadhel Idan (Institute of Advanced Engineering and Science, 2021)
Multiple integral representation (MIR) has been used to represent studying the effect of temperature on the amount of nonlinear creep on the semi-crystalline polypropylene (PP) under the influence of axial elastic stress. To complete this research, the kernel functions were selected, for the purpose of performing an analogy, and for arranging the conditions for the occurrence of the first, second and third expansion in a temperature range between 20 °C-60 °C, i.e., between the glass transition and softening temperatures, within the framework of the energy law. It was observed that the independent strain time increased non-linearly with increasing stress and non-linearly decreased with increase in temperature, although the time parameter increased non-linearly with stress and temperature directly. In general, a very satisfactory agreement between theoretical and practical results on the MIR material was observed.